Development and characterization of a theranostic micelles system using TPGS with docetaxel and coumarin-6: a dual polymeric nanocarrier system - Ching, L.H.; Mahmood, Syed; Raihana Z., Edros; Rajaletchumy, Veloo Kutty (Universiti Malaysia Pahang, 2018)
Theranostic micelles and polymeric nanocarrier-based drug delivery system are well known techniques that involve a diagnostic agent in polymeric micelles for a combination of therapy by using a co-delivery approach which can help in detection of a cancer cell in an early stage, increase killing effect and suppress multi-drug resistance (MDS) for better therapeutic effectiveness. The aim of this study is to develop a dual modality micellar system using D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as a nanocarrier for co-delivery of docetaxel as a model chemotherapeutic drug and coumarin-6 as a model fluorescence imaging agent for simultaneous cancer imaging and therapy in an early stage. The theranostic micelles were prepared by a solvent casting method and characterized by their particle size, drug loading, drug encapsulation efficiency (EE) and in-vitro drug release profile. These dual modality micellar system TPDC6 micelles were successfully developed with average particle size of 79.59±0.57 nm in diameter and drug loading up to 15.46±1.02 (EE of 78.99±1.26) and 9.83±0.76 (EE of 36.20±0.89) for docetaxel and coumarin-6 respectively. Besides, the in-vitro drug release profile of the micelles revealed a desired sustained and controlled drug release manner for both docetaxel (21.62±0.36) and coumarin-6 (10.70±0.46). In conclusion, the micelles size obtained is in the favourable range for passive targeting through enhanced permeability and retention (EPR) effect and the drug loading and encapsulation efficiency attained are adequate for therapy and diagnosis purposes on cancer cells. This dual modality system is taking great advantages for tumour imaging and inhibition of tumour growth which is very important for early cancer detection.